Deep brain stimulation in Parkinson’s disease - the review - Jasielski, Patryk Piotr; Piędel, Faustyna; Szumna, Klaudia; Madras, Dominika; Rocka, Agata (Journal of Education, Health and Sport, 2020)
Introduction: Parkinson’s disease (PD) is a common neurodegenerative disorder and is the second most common neurodegenerative disease after Alzheimer’s disease. The clinical features are associated with motor symptoms: tremor, rigidity, and bradykinesia with postural instability. PD is also associated with many non-motor symptoms, and these often precede the motor symptoms by years or even decades. In general, treatment is based on usage of medicaments which increase a level of dopamine. Surgical therapy is reserved for more advanced cases. Objective: To review currently available data on PubMed about a surgical treatment of Parkinson’s disease and future prospects. Abbreviated description of the state of knowledge: Surgical therapy is typically reserved for bradykinesia, rigidity and tremor in patients who no longer respond to medication in a predictable manner or who suffer medication-induced dyskinesias. Currently, the most common surgical treatment for Parkinson’s disease is deep brain stimulation (DBS). Ablative procedures like radiofrequency, radiosurgery and focused ultrasound are also utilized for select tremor symptoms. We also analyzed future prospects including cells transplantation. DBS decreases a level of disability, depression and increases quality of life. It should to take under consideration in early as well as advanced PD. Conclusions: PD is still incurable, however both pharmacological and surgical treatment can stifle the progression of disease for years and increase quality of life. New methods of treatment are promising. However, the further research about possible therapy is required.